A comparative study between 7 Stage and 4 Stage Systems Development Life Cycle (SDLC) Models - Sabat, Kali charan; Sampat, Brinda (IJRDO -Journal of Computer Science Engineering, 2016)
The paper describes the commonly used 7 stage Systems Development LifeCycle (SDLC) model and a different compressed 4 stage SDLC model. It also comparesand contrast the 7 Step Model with the selected 4 stage model.